Quantum chemical, spectroscopic and X-ray diffraction studies of 5-methoxy-2-({4-[3-methyl-3-mesityl-cyclobutyl]-thiazol-2-yl}-hydrazonomethyl)-phenol - Saracoglu, Hanife; Cukurovali, Alaaddin (Elsevier, 2013)
The title molecule, 5-methoxy-2({4-[3-methyl-3-mesityl-cyclobutyl]-thiazol-2-yl)-hydrazonomethyl)-phenol (C-25 H-29 N-3 O-2 S), was prepared and characterized by elemental analysis, H-1 NMR, C-13 NMR, IR and X-ray single-crystal determination. The compound, crystallizes in the monoclinic space group P2(1)/c with a = 18.9647(4)angstrom, b = 11.0203(3) angstrom, c = 10.8562(2)angstrom and beta = 91.546(2)degrees. In addition to the molecular geometry from X-ray determination, vibrational frequencies and gauge, including atomic orbital (GIAO) H-1 and C-13 NMR chemical shift values of the title compound in the ground state, were calculated using the Hartree-Fock and density functional methods with the 6-31G(d, p) basis set. The calculated results show that the optimized geometries can well reproduce the crystal structure. Besides, the theoretical vibrational frequencies and chemical shift values show good agreement with experimental values. The calculated first hyperpolarizability of the title compound are greater than those of urea. DFT calculations of the molecular electrostatic potentials, frontier molecular orbitals and thermodynamic properties of the title compound were carried out at the B3LYP/6-31G(d, p) level of theory. (c) 2013 Published by Elsevier B.V.
Keywords: Computational chemistry; X-ray structure determination; NMR spectroscopy; Frontier molecular orbitals; Molecular electrostatic potential